HUBUNGAN KECEMASAN DENGAN KEJADIAN TENSION - TYPE HEADACHE PADA MAHASISWA KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA TAHUN 2020 - ALDO KRESNA MAHENDRA; NELLI MURLINA (LP2MTBM MAKARIOZ, 2021)
Tension-type headache (TTH) is one of the most common headache and most common forms of primary headaches.According to the International Association for the Study of Pain (IASP) nearly 80% of all people in their lifetime haveexperienced episodic TTH and 3% have chronic TTH. TTH has comorbidities with many psychiatric disorders includinganxiety, although the characteristics of the individual itself largely determine the relationship between anxiety and TTH.Medical students have health problems and high stress levels especially those in their final semester. The demands andpressures of a tough final project have an impact on high levels of anxiety and stress in medical students. To determine therelationship between anxiety and events. Tension-Type Headache in Medical Faculty students of the University ofMuhammadiyah, North Sumatra in 2020. Using a descriptive analytic observational method and a cross sectional studyapproach with a purposive sampling technique that is samples will be selected and considered subjectively in the hope thatthey can provide adequate information in answering research questions. From the results of statistical analysis this studyshowed that there was a significant relationship between anxiety and the incidence of TTH in FK UMSU students with a pvalue = 0.0001. There is a significant relationship between anxiety and the incidence of TTH in FK UMSU students in 2020.